2019
DOI: 10.1002/jcp.28596
|View full text |Cite
|
Sign up to set email alerts
|

NLRC5 negatively regulates LTA‐induced inflammation via TLR2/NF‐κB and participates in TLR2‐mediated allergic airway inflammation

Abstract: NLRC5, the largest member of the Nod-like receptor (NLR) family, has been reported to play a pivotal role in regulating inflammatory responses. Recent evidence suggests that NLRC5 participates in Toll-like receptor (TLR) signaling pathways and negatively modulates nuclear factor-κB (NF-κB) activation. In this study, we investigated the interaction between NLRC5 and TLR2 in the NF-κB inflammatory signaling pathway and the involvement of NLRC5 in TLR2-mediated allergic airway inflammation. We knocked down TLR2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Besides, the protein level of NLRC5 decreased in USP14knockdown cells, which might be caused by the enhanced ubiquitination and increasing degradation of NLRC5, as USP14-mediated deubiquitination was attenuated after USP14 was down-regulated. These results strongly suggested that USP14/NLRC5 played a negative role in the inflammatory response induced by Ti particles and was consistent with the previous studies which found that NLRC5 negatively regulated the NF-κB signaling pathway and USP14 shaped NLRC5 function and modulated NF-κB activation switch [23,25,27].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Besides, the protein level of NLRC5 decreased in USP14knockdown cells, which might be caused by the enhanced ubiquitination and increasing degradation of NLRC5, as USP14-mediated deubiquitination was attenuated after USP14 was down-regulated. These results strongly suggested that USP14/NLRC5 played a negative role in the inflammatory response induced by Ti particles and was consistent with the previous studies which found that NLRC5 negatively regulated the NF-κB signaling pathway and USP14 shaped NLRC5 function and modulated NF-κB activation switch [23,25,27].…”
Section: Discussionsupporting
confidence: 92%
“…It strongly inhibits NF-κB-dependent responses by interacting with IKKα and IKKβ and blocking their phosphorylation [23]. NLRC5 negatively regulates inflammatory response via a TLR2/NF-κB pathway in macrophages and also participates in TLR2-mediated allergic airway inflammation [25]. Meanwhile, enhanced TLR-induced NF-κB signaling was detected in NLRC5 deficient mice [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the role of NLRC5 in Toll‐like receptor (TLR) signaling is also unclear. NLRC5 has been demonstrated to negatively regulate the TLR2/NF‐ κ B axis pathway upon lipoteichoic acid stimulation 73 and NLRC5 deficiency was shown to up‐regulate the TLR4/NF‐ κ B axis‐mediated inflammatory response 7,70,74 . However, multiple groups have shown that deletion of Nlrc5 in murine systems does not affect responses to TLR2, TLR3 and TLR9 ligands 33,72 .…”
Section: Possible Nlrc5 Functions Beyond Mhc‐i Pathwaymentioning
confidence: 99%
“… 2 The mechanism underlying the damage induced by cerebral ischemia-reperfusion is complicated, but two factors, inflammation and ROS, are still recognized to be crucial parts in the process. 15 17 NLRC5 has been shown to relieve allergic airway inflammation, 18 and suppress the NF-κB pathway to alleviate the inflammatory reaction. 19 In the present paper, levels of TNF-α, IL-6 and IL-1β were found to be reduced by overexpression of NLRC5, and together with published data, these results indicate that NLRC5 may inhibit the inflammatory reaction in cerebral ischemia-reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%